Numerical Simulation Analysis of the Seismic Performance of Precast Bridge Piers - Jia Wang (Mathematical Problems in Engineering, 2022)
Precast technology is increasingly favoured by bridge engineers, and the seismic performance of precast bridge piers urgently needs to be addressed. Precast piers have a complex load-bearing mechanism, and their design method has not been clearly determined. Fibre plastic hinge theory can satisfactorily analyse the seismic performance of precast piers. In this study, the seismic performance of precast piers is analysed through numerical simulation of pier columns based on the pseudostatic testing of a set of existing precast piers and combined with fibre plastic hinge theory. The results show the following: With reasonable constructional measures, precast piers connected by grouted sleeves indeed have seismic performance similar to that of cast-in-place components. Finite-element programs can be employed to simulate the mechanical properties of steel rebars before yielding well but not those after yielding or under fatigue. When fibre plastic hinges are used for finite-element analysis, if the fibre cross-section is reasonably divided, the length of the plastic hinge has little influence on the results; otherwise, too densely distributed plastic hinges may lead to nonconvergence of the results in a later working condition. The plastic hinge method recommended in this paper, especially the sectional fibre-cross-section division method, can obtain the plastic hinge performance state, it can help save the test cost and make up for the shortage of test data.